Modification of Microcrystalline Cellulose (MCC) Derived from Liberica Coffee Husk Using Saponins for Controlled Release of Dexamethasone - Tiara, Tiara; Yusnaidar, Yusnaidar (Pendidikan Kimia FKIP Universitas Jambi, 2025)
Microcrystalline cellulose (MCC) is a partially depolymerized cellulose derivative obtained through the hydrolysis of α-cellulose. However, MCC has limitations in drug delivery systems, particularly for poorly water-soluble (hydrophobic) drugs; therefore, MCC modification is required to improve the loading and delivery efficiency of such compounds. This study aimed to modify MCC produced from the hydrolysis of Liberica coffee husk cellulose to enable its application as a carrier for hydrophobic drugs. The modification was carried out using saponins, followed by dexamethasone loading into MCC–saponin and unmodified MCC using ethanol as the solvent, with incubation for 24 h. The MCC–saponin system exhibited a substantially higher dexamethasone loading capacity (23.436 mg/g) than unmodified MCC (6.768 mg/g). In vitro drug release results further showed that dexamethasone release from MCC–saponin increased within 60–180 min.